PROBLEMATIC TIKTOK USE AND ITS ASSOCIATION WITH DEPRESSION, ANXIETY AND SLEEP DISTURBANCE IN ADOLESCENTS: A SYSTEMATIC REVIEW - Natalia Ziółkowska,; Natalia Kruszewska,; Michał Cholewiński,; Paweł Szajewski,; Alicja Pełszyk,; Agata Pluta,; Justyna Kącikowska,; Daria Marciniak,; Justyna Łapicka,; Natalia Rosół, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: TikTok is one of the most popular social media platforms among adolescents. Application works by showing an endless stream of short, absorbing videos, which are personalized for the user by an AI-algorithm. Although its main function is to provide entertainment, it is indicated that compulsive use of the application, termed Problematic TikTok Use (PTU), is associated with adverse mental health outcomes, including depression, anxiety and sleep disturbances.Materials and methods: A literature review was gathered using PubMed, Google Scholar, ScienceDirect and related databases, focusing on the literature specifically examining TikTok and its effects on adolescents, published between 2020 and 2025.Key findings and conclusions: Research shows associations between Problematic TikTok Use and increased risk of depression, anxiety and sleep disorders among adolescents. Several mechanisms responsible for the negative effects of PTU are distinguished, such as social comparison, fear of missing out, doomscrolling, information overload, feedback and reward-seeking behaviors, emotional contagion and nighttime screening. Users with higher screen time show more negative effects. Longitudinal and cross-cultural studies are needed to further investigate the mechanisms and ways of prevention as the current literature is limited by cross-sectional designs, methodological heterogeneity and reliance on self-report.